Effect Of Indium On Microstructure And Intermetallic Compound Formation During Isothermal Aging Of Sncu Solder Alloy - Khusaini, Nur Nadirah Mohd (2018)
Solder is the interconnect material serving both electrical and mechanical connections between components and substrate in electronic devices. Concern over the toxicity of lead sparked intense focus on finding alternative lead-free solders to replace the traditional Sn-Pb solder. Among the lead-free solder alloy, Sn-Cu alloy has relatively good physical and mechanical characteristics, low cost, and is currently being used in wave soldering. However, Sn-0.7Cu solder alloy has higher melting point (227°C) compared to SnPb (183°C). Indium was added into Sn-0.7Cu-0.05Ni-Ge (SN100C) solder alloy in this work to reduce the melting point, but the effect to IMC growth during thermal aging need to be evaluated. SN100C and indium added (0.5, 1, 1.5 and 2 wt%) solder was prepared via casting process. The solder alloys were reflowed onto Cu substrate at 270°C for 10 seconds. Elemental composition was determined using X-ray fluorescence (XRF) technique while melting point of solder alloys was determined using differential scanning calorimetry (DSC). Wetting balance test and spreading test were used to evaluate wettability. Meanwhile thermal aging was done for 100, 250 and 500 hours at 150°C and 180°C. Respectively, the microstructure of bulk solder and the IMC formed at interface between solder and Cu substrate were observed using scanning electron microscopy (SEM) equipped with electron dispersive x-ray (EDX). The wettability of solder alloys increased with increasing amount of In. Addition of In after aging resulted in the formation of (Cu,Ni)6Sn5 and Cu3Sn+Ni+In, seems to reduce formation of Cu6Sn5 and Cu3Sn IMC, and refined primary β-Sn dendrites. Further addition of 2 wt.% In resulted in formation of Sn-Cu-Ni-In IMC. The addition of 2 wt.% In gave the lowest growth rate of IMC which was 3.364 x 10-13 (cm2/s) while SN100C gave highest growth rate at 4.096 x 10-13 (cm2/s). The activation energy for SN100C-2In at 53 kJ/mol was the highest compared to SN100C 29.5 kJ/mol. From the result, it can be concluded that indium addition could lead to a finer β-Sn grain, increased hardness, improved wettability and supressed Cu3Sn IMC layer during isothermal aging which could increase the reliability of solder joint.